Anti-cytoplasmic anti-bodies of neutrophils and monocytes - Appreciation of their use in clinical practise - Caldas Amaral, Sandra Margarida (1999)
Ten years passed over the discovery of ANCA - Antineutrophil Cytoplasmic Antibodies - without the criteria that stablish a clinicai relation concerning the study of the vasculitic sindromes. This article reviews the importance of ANCA in vasculitis, with special attention devoted to physiological, diagnostic and prognostic implications.